Relationship Between the Brain Natriuretic Peptide (BNP) Level and Prognosis of Diabetic Nephropathy with Microalbuminuria: A 7-Year Follow-Up Study - Seki, Naoto; Matsumoto, Tsuyoshi; Fukazawa, Motoharu (Hormone and Metabolic Research, 2018)
The aim of the study was to examine the relationship between the brain natriuretic peptide (BNP) level and prognosis of diabetic nephropathy. The subjects were 100 Japanese outpatients with type 2 diabetes mellitus with microalbuminuria. Associations between metabolic parameters at baseline, including BNP, and prognosis of diabetic nephropathy (progression of diabetic nephropathy, cardiovascular events, and death) were examined for 7 years. In Cox proportional hazard analysis, HbA1c, albumin-creatinine ratio (ACR) and BNP were identified as significant factors for progression of diabetic nephropathy (p=0.033, p=0.037, and p=0.044, respectively), BNP was identified as significant factor for cardiovascular events (p=0.046), and estimated glomerular filtration rate (eGFR) and BNP were identified as significant factors for death (p=0.046 and p=0.048, respectively). In Kaplan–Meier analysis, risks of progression of diabetic nephropathy, cardiovascular events, and death were significantly different between patients with a low and a high BNP level (p=0.046, p=0.002, and p=0.025, respectively). ROC curve analysis gave cutoff values for BNP of 14.9 pg/ml for progression of diabetic nephropathy, 16.3 pg/ml for cardiovascular events, and 17.6 pg/ml for death (p=0.047, p=0.035, p=0.018, respectively). In conclusion, the BNP level is associated with prognosis in diabetic nephropathy.
Keywords: diabetic nephropathy; microalbuminuria; brain natriuretic peptide